Temporal trends of concentrations of per- and polyfluoroalkyl substances among adults with overweight and obesity in the United States: Results from the Diabetes Prevention Program and NHANES. (December 2021) - Lin, Pi-I D.; Cardenas, Andres; Hauser, Russ; Gold, Diane R.; Kleinman, Ken P.; Hivert, Marie-France; Calafat, Antonia M.; Webster, Thomas F.; Horton, Edward S.; Oken, Emily
Highlights: The study examined trend of blood concentrations of PFAS among U.S. adults. Geometric means of PFOS, PFOA, PFHxS, EtFOSAA and MeFOSAA declined since 2000. Geometric means of PFNA increased from 2000 to 2010. Male had higher geometric means of PFOS and PFNA than female. Black had higher geometric means of PFOS and PFNA than white participants. Abstract: Background: Understanding the temporal trends and change of concentrations of per- and polyfluoroalkyl substances (PFAS) is important to evaluate the health impact of PFAS at both the individual- and population-level, however, limited information is available for pre-diabetic adults in the U.S. Objectives: Determine trends and rate of change of plasma PFAS concentrations in overweight or obese U.S. adults and evaluate variation by sex, race/ethnicity, and age. Methods: We described temporal trends of plasma PFAS concentrations using samples collected in 1996–1998, 1999–2001, and 2011–2012 from 957 pre-diabetic adults enrolled in the Diabetes Prevention Program (DPP) trial and Outcomes Study (DPPOS) and compared to serum concentrations from the National Health and Nutrition Examination Survey (NHANES 1999–2000, 2003–2016, adults with BMI ≥ 24 kg/m 2 ). We examined associations between participants' characteristics and PFAS concentrations and estimated the rate of change using repeated measures in DPP/DPPOS assuming a first-order elimination model. Results: Longitudinal measures of PFAS concentrations in DPP/DPPOS individuals were comparable to NHANES cross-sectional populational means. Plasma concentrations of perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid, perfluorohexanesulfonic acid (PFHxS), N-ethyl-perfluorooctane sulfonamido acetic acid (EtFOSAA), and N-methylperfluorooctane sulfonamido acetic acid (MeFOSAA) started to decline after the year 2000 and concentrations of perfluorononanoic acid (PFNA) increased after 2000 and, for NHANES, decreased after 2012. We consistently observed higher PFOS, PFHxS and PFNA among male, compared to female, and higher PFOS and PFNA among Black, compared to white, participants. The estimated time for concentrations to decrease by half ranged from 3.39 years for EtFOSAA to 17.56 years for PFHxS. Discussion: We observed a downward temporal trend in plasma PFOS concentrations that was consistent with the timing for U.S. manufacturers' phaseout. Male and Black participants consistently showed higher PFOS and PFNA than female and white participants, likely due to differences in exposure patterns, metabolism or elimination kinetics.